Screening for Fabry disease in patients with left ventricular noncompaction - Azevedo, Olga (2019)
It is unclear whether left ventricular noncompaction (LVNC) is a distinct cardiomyopathy or a morphologic manifestation of different cardiomyopathies. We previously reported a case of LVNC in a Fabry disease (FD) patient, but it remains to be clarified whether LVNC is a cardiac manifestation of FD, a coincidental finding or an overdiagnosis, which has major therapeutic implications. This study aims to determine the prevalence of FD among patients with LVNC.